Multiparameter Phase I trials: a tool for model-based development of targeted agent combinations – example of EVESOR trial. (May 2015) - El-Madani, Mevidette; Hénin, Emilie; Lefort, Thibaud; Tod, Michel; Freyer, Gilles; Cassier, Philippe; Valette, Pierre-Jean; Rodriguez-Lafrasse, Claire; Berger, Francoise; Guitton, Jérome; Lachuer, Joel; Slimane, Khemaies; et al.
ABSTRACT : Optimal development of targeted drug combinations is one of the future challenges to be addressed. Computerization and mathematical models able to describe biological phenomena and to simulate the effects of changes in experimental conditions may help find solutions to this issue. We propose the concept of 'multiparameter trials', where biological, radiological and clinical data required for modeling purpose are collected and illustrated by the ongoing academic EVESOR trial. The objective of the model-based work would be the determination of the optimized doses and dosing schedules of everolimus and sorafenib, offering the maximization of the predicted modeled benefit/toxicity ratio in patients with solid tumors. It may embody the 'proof of concept' of model-based drug development of anticancer agent combinations.